PROPOSED MARKETING STRATEGY FOR PRE-LOVED LUXURY FASHION BRAND IN MOBILE APP - Angelica/ 29116417, Vionna
PROPOSED MARKETING STRATEGY FOR PRE-LOVED LUXURY FASHION BRAND IN MOBILE APP VIONNA ANGELICA NIM : 29116417 Master’s Programme, Bandung Institute of Technology, 2018 Thesis Counsellor : Dr. Ir. MustikaSufiatiPurwanegara, M.Sc. ABSTRACT Introduction - Dubois (1993) said that luxury is identical with perception of comfort, beauty, and sumptuous lifestyle. Thus, the definition of luxury fashion brand itself is goods that has brand image and perceived as something that has uniqueness, quality, hedonic, conspicuousness, and extended self and could give comfort, beauty, and sumptuous lifestyle (Vigneron and Johnson, 2004). Online visual display nowadays is one of marketer’s channels to promote the product. In terms of exclusivity, there is only few channels that has been used by marketer, such as website of the luxury brand itself, Instagram, Facebook, and Youtube. This research of online luxury fashion brand is focused on one mobile app, named Instagram. Instagram was chosen because Instagram usagehas increased over time, especially in Indonesia. This research is focused on used luxury fashion brands in on line stores on Instagram. There is an increase in the used luxury fashion industry but there is a decrease for the "X" online shop. Exploratory preliminary research is carried out and it can be concluded that the root cause of the decline in sales occurs because the visual appearance of luxury fashion brands on line is not very attractive. The purpose of this study was to determine the cause of the decline in sales of "X" and provide a solution for "X" based on these causes. Method - The method used is experimental design. Respondents of this study were selected using non-probability sampling, namely judgmental sampling. This study uses a pupil movement tracker, called Gaze Point, which is intended for potential consumers. To get quantitative experimental data, the minimum respondents needed are 39 people (Pernice and Nielsen, 2009). Users are given oral questions and VALS tests, after they complete the experiment using an eye tracker. This research is only done for consumers in Bandung. Respondents are women with upper middle income and have bought used luxury fashion bags because the percentage of women spending on luxury goods is higher than men. Interviews were also conducted to loyal consumers to find out the motivation to shop at the "X" Online Shop. Some alternative solutions are built based on experimental design results, consumer lifestyles, and loyal consumer motivation. The proposed solution was then made into an implementation plan and given to the owner of an on-line "X" luxury bag store. Findings – The findings of this research are used luxury fashion branded goods on line currently developing rapidly. Respondents who look longer at a post photo show that respondents tend to be more interested in the post. Promotions through photo posting and consumer motivation refer to improvements in the marketing mix. Keywords : Online marketing, luxury branded goods, pre-loved luxury branded bag, eye tracking .